FitBit Watch Along with A Monitoring Body Temperature Application - KUMARAVELU, SHARRADAYINI; AZLINA BAHARI (Progress in Engineering Application and Technology, 2021)
The term Fitbit refers to exercising tracker devices manufactured and bought by way of Fitbit Incorporated. Designed to help clients take control of their health and fitness, Fitbit units track facts such as step counts and power burned, amongst other functions. These devices are geared up with unique sensors, algorithms, and accompanying mobile phone apps. With current advances in mobile sensor technology, privately gathered bodily project facts can be used as an addition to cutting-edge methods for health records collection in research. Furthermore, statistics gathered from these gadgets have feasible purposes in affected person diagnostics and treatment. With a developing vary of numerous brands, there is a select for an overview of gadget sensor support, as well as machine applicability in research projects. The purpose of this project is to develop a Fitbit watch that can be used to keep track the amount of calories burnt and distance covered by walking and also to monitor the patient’s body temperature from time to time via an application through the mobile. The project is built using a TTGO-T Display ESP 32 microcontroller unit. The heart rate sensor and temperature sensor each would be programmed before it is combined into one programme to be downloaded into the microcontroller. The system provides the user interface that can be used on any smartphone to monitor the temperature data. By implementing this system, I believe we can have healthier people and also people who are alert with their body temperature.